A Comparative Study on Criminal Sanction Against Drugs Offenders - Monalisa Monalisa; Sri Rahayu; Dheny Wahyudhi (Jambe Law Journal, 2019)
This article seeks to compare the criminal sanction regulation upon narcotics offences between Indonesian Narcotics Law and Singapore Drugs Act. Indonesia and Singapore have shared commitments to eradicate drugs offences in its respective country. Despite their similarity, however, both countries also have different approach to be applied in their respective laws to eradicate drugs offence. Methodogically normative, a comparative is exercised in order to reveal to what extent do Indonesia and Singapore have similarities and differences in applying sanction upon drug offenders and how both countries manage to eradicate the offence. Despite its success to significantly decrease number of narcotics offences due to its strict approach in its appliaction and resulting in deterrence effect for criminal offenders, Singapore shall not be compared to Indonesia. Not only because both countries have different system of law but also face different character of region. Besides, Indonesia is much bigger than Singapore. Despites sharing differences, both country may learn, share, and cooperate each other in order to more effectively eradicate drugs offences in the both coutries